PEMENUHAN HAK-HAK ANAK PADA KELUARGA PEKERJA MIGRAN INDONESIA PERSPEKTIF MAQASID AL-SYARI'AH - Ahmad Dusturi; Muktamar; Nuruddin; Apipuddin (QAWWAM : Journal for gender mainstreaming, 2026)
This study examines the fulfillment of children's rights in Indonesian Migrant Worker families in Lelong Village, Central Praya District, from the perspective of maqasid al-shari'ah, focusing on the rights to livelihood (nafkah), education, and custody (hadhanah). Using a qualitative case study approach, data were obtained through in-depth interviews, observation, and documentation with five PMI families. The findings show that the fulfillment of children's rights is partial and varies across families. The right to livelihood is fulfilled but fluctuates depending on the continuity of remittances. The right to education is formally fulfilled but faces obstacles in academic supervision. The right to custody is functionally fulfilled by substitute caregivers but lacks optimal emotional closeness. From the maqasid al-shari'ah perspective, the fulfillment of children's rights in PMI families has not yet fully realized the ideal objectives of shari'ah, particularly in protecting the soul (hifz al-nafs), intellect (hifz al-'aql), and lineage (hifz al-nasl). This study also reveals the gender dimension, where female caregivers (mothers, grandmothers, or other female relatives) bear a double burden in substitute caregiving while also managing the household economy.